2013
DOI: 10.1186/1475-2840-12-122
|View full text |Cite
|
Sign up to set email alerts
|

24-hour central aortic systolic pressure and 24-hour central pulse pressure are related to diabetic complications in type 1 diabetes – a cross-sectional study

Abstract: BackgroundNon-invasive measurements of 24 hour ambulatory central aortic systolic pressure (24 h-CASP) and central pulse pressure (24 h-CPP) are now feasible. We evaluate the relationship between 24 h central blood pressure and diabetes-related complications in patients with type 1 diabetes.MethodsThe study was cross-sectional, including 715 subjects: 86 controls (C), 69 patients with short diabetes duration (< 10 years), normoalbuminuria (< 30 mg/24 h) without receiving antihypertensive treatment (SN), 211 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
1
15
1
1
Order By: Relevance
“…16 We have previously found 24-hour measurements of CASP and CPP obtained with a different device (BPro, HealthStats, Singapore) to be associated with diabetic complications (albuminuria degree, presence of CVD, retinopathy, and autonomic dysfunction) in this cohort. 10 With this study, we found no association between central hemodynamics and retinopathy but a significant association with presence of autonomic neuropathy (heart rate variability during deep breathing; data not shown). Measurements with BPro during 24 hours may provide a more precise estimate of risk, as compared with office blood pressure, whereas office measurements with the SphygmoCor device, which has been tested much more, are faster to perform and provides the ability to estimate SEVR.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…16 We have previously found 24-hour measurements of CASP and CPP obtained with a different device (BPro, HealthStats, Singapore) to be associated with diabetic complications (albuminuria degree, presence of CVD, retinopathy, and autonomic dysfunction) in this cohort. 10 With this study, we found no association between central hemodynamics and retinopathy but a significant association with presence of autonomic neuropathy (heart rate variability during deep breathing; data not shown). Measurements with BPro during 24 hours may provide a more precise estimate of risk, as compared with office blood pressure, whereas office measurements with the SphygmoCor device, which has been tested much more, are faster to perform and provides the ability to estimate SEVR.…”
Section: Discussioncontrasting
confidence: 50%
“…9 Recently, we demonstrated 24-hour values of central blood pressure measured with the BPro device (HealthStats, Singapore) to be associated with diabetic complications in our study cohort. 10 In this study, we expand these analyses to the cross-sectional relationship between presence of CVD or albuminuria at baseline and estimates of SEVR and central blood pressure measured in the office with the SphygmoCor device (Atcor Medical, Sydney, Australia). Moreover, we are the first to evaluate the prognostic value for development of end-stage renal disease (ESRD) and all-cause mortality in relation to office measurements of central hemodynamics in patients with type 1 diabetes.…”
Section: Original Articlementioning
confidence: 99%
“…In adult, T1DM patients from the STENO‐cohort DR was significantly related to 24 hours central aortic systolic pressure, 24 hours central PP, 24 hours SBP, and long diabetes duration. Arterial damage caused by diabetes seems to be a later complication not relevant before 10 years of diabetes duration which might explain the association between DR and lower PP in our patients.…”
Section: Discussionmentioning
confidence: 62%
“…Arterial stiffness is known to be higher in diabetic human tissue post-mortem [42] as well as in the arteries [43-45] and myocytes [44] of diabetic patients. These effects are commonly attributed to increased fibrosis [44], deposition of advanced glycation end-products [44,45], increased oxidative stress [45] or low-grade inflammation [43]. The absence of any difference of blood pressure indices between STZ and SHAM rat hearts probably reflects the difference between acute (present study) and chronic diabetes (human patients).…”
Section: Discussionmentioning
confidence: 99%